Tom Lake : a novel - Patchett, Ann (Reese's book club., 2023)
Recalling the past at her daughters' request, Lara tells the story of a famous actor with whom she shared both a stage and a romance, which causes her daughters to examine their own lives and reconsider the world and everything they thought they knew.